Labour market asymmetries in a monetary union - Torben M. Andersen; Martin Seneca (Danmarks Nationalbank, 2008)
This paper takes a first step in analysing how a monetary union performs in the presence of labour market asymmetries. Differences in wage flexibility, market power and country sizes are allowed for in a setting with both country-specific and aggregate shocks. The implications of asymmetries for both the overall performance of the monetary union and the country-specific situation are analysed. It is shown that asymmetries are not only critical for country-specific performance but also for the overall performance of the monetary union. A striking finding is that aggregate output volatility is not strictly increasing in nominal rigidities but hump-shaped. Moreover, a disproportionate share of the consequences of wage inflexibility may fall on small countries. In the case of country-specific shocks, a country unambiguously benefits in terms of macroeconomic stability by becoming more flexible, while this is not necessarily the case for aggregate shocks. There may thus be a tension between the degree of flexibility considered optimal at the country level and at the aggregate level within the monetary union.
Keywords: E30; E52; F41; 330; wage formation; nominal wage rigidity; staggered contracts; monetary policy; monetary union; business cycles; shocks; Währungsunion; Lohnbildung; Lohnrigidität; Geldpolitik; Theorie